ETHNOMATHEMATICS-BASED LEARNING OF THE EARTH BALL MONUMENT FOR STUDENTS OF CLASS VII OF SMP NEGERI 2 WERMAKTIAN - Manutmasa, Hawila Dorenci; Samuel Urath; Yoseph Watratan (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2025)
Ethnomathematics-based learning is currently highly relevant and aligns well with the students' environmental context. This approach facilitates learning by connecting with students’ experiences and perceptions. This study aims to examine the improvement in learning outcomes of Grade VII students at SMPN 2 Wermaktian through ethnomathematics-based learning centered on the "Bola Bumi" monument. The research method employed is a descriptive qualitative approach. Data collection techniques include observation (observing student learning activities and teacher instruction), structured interviews with teachers and students, and tests (assessing learning outcomes based on indicators developed by the researcher). Data analysis follows the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that implementing the model based on ethnomathematics progressively enhances students’ learning activities. Student activity significantly increased from 36.7% in the first meeting to 96.7% in the third meeting, while teacher activity improved from 46.7% to 100%, reflecting enhanced abilities to motivate, facilitate interaction, and guide discussions. Additionally, there was a notable improvement in the percentage of students achieving learning mastery, rising from 4.2% in the initial test to 83.4% in the final test. This improvement is attributed to the ethnomathematics-based  approach, which boosts students’ enthusiasm for learning by connecting the material with local culture. Moreover, this approach successfully elevated students' active participation to a very high category, demonstrating that integrating mathematics with culture makes learning more meaningful, relevant, and enjoyable for students.